On the Chinese Concept of “Wild Words and Fancy Language” and its Interpretation in Japan - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2004)
The Japanese concept of the term “kyōgen kigo” or “kyōgen kigyo”, which in English means “wild words and fancy language”, has influenced Japanese literary thought to a considerable degree. The originally Buddhist term that became popular in China and then in Japan was coined by the Tang dynasty’s poet Bai Juyi, who first spoke disapprovingly and then contemptuously about novels or any kind of fiction from both the Buddhist and the Confucian standpoints. This article is a discussion of the metamorphosis in the meaning of this term “kyōgen kigo” in Japan.By kyōgen kigo Bai Juyi meant to criticize secular poetry, particularly for its unforgivable vanity hidden beneath cascades of elaborate words. In Japan waka poetry remained untainted by such pretensions, and the effect of waka verses on its readers has been said to be similar to the effect that dhāranī, the mystic verses of India, have on their reader. However, in other Japanese literature, kyōgen kigo flourishes were abundant and expanded from literature to music and to the arts in general. In the course of time the conflict between the duties of Buddhism and the pleasure derived from art was transformed into a justification of the latter and even into promotion of art as a means to religious fulfilment. This paper follows the shift in the connotations of kyōgen kigo in Japan,as represented in Buddhist-influenced medieval literature that in spite of the religious moralizing also reflects kyōgen kigo flourishes.